2002
DOI: 10.1248/cpb.50.1011
|View full text |Cite
|
Sign up to set email alerts
|

Re-revision of the Stereo Structure of Piperidine Lactone, an Intermediate in the Synthesis of Febrifugine

Abstract: The stereo structure of piperidine lactone (3), an intermediate of the antimalarial agent febrifugine ((؉)-1) prepared by a synthetic method, was re-revised to the cis-form from the transform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Some of the early synthesis procedures encountered various problems because of uncertainty regarding the absolute stereochemistry. It was found that under certain conditions febrifugine and isofebrifugine could interconvert [29]. Recently, an elegant review was published that described the chemical complexity of the molecules involved and the problems encountered during the synthesis of febrifugine, isofebrifugine and halofuginone [30].…”
Section: The Origin Of Halofuginone and Its Synthesismentioning
confidence: 99%
“…Some of the early synthesis procedures encountered various problems because of uncertainty regarding the absolute stereochemistry. It was found that under certain conditions febrifugine and isofebrifugine could interconvert [29]. Recently, an elegant review was published that described the chemical complexity of the molecules involved and the problems encountered during the synthesis of febrifugine, isofebrifugine and halofuginone [30].…”
Section: The Origin Of Halofuginone and Its Synthesismentioning
confidence: 99%